(untitled) (Global Scientific Review, 2024)
This paper studies Korea’s foreign policy in Central Asia from the perspective of regional cooperation. It analyzes the past, the present and the current state of cooperation, including after the 1990s when the Central Asian countries became independent. An important element of this study is a detailed analysis of cooperation between Korea and Central Asia on a multilateral and bilateral scale. Asymmetries in two-way exchanges between Korea and Central Asian countries encourage Korea to implement specific projects suitable for its partners. At the same time, Korea is leveraging multilateral cooperation and anticipating future prospects for cooperation in key areas such as health, environment, and digital policy. Importantly, the “KoreaCentral Asia” forum will help strengthen cooperation between Korea and Central Asia. Finally, future prospects and some suggestions on expanding the scope of cooperation were offered.